Islamic economics under Wilāyat al-Faqīh: Doctrinal foundations, governance structures, and the political economy of sanctions in the Islamic Republic of Iran - Husaini, Taqi (Journal of Islamic Economic Insights, 2026)
This letter examines the intersection of Islamic economic thought, the constitutional doctrine of Wilāyat al-Faqīh (Guardianship of the Jurist), and the sustained impact of international economic sanctions on the Islamic Republic of Iran. Drawing on institutional economics, political economy, and Islamic jurisprudence (fiqh), this study argues that Iran's distinctive governance architecture, in which supreme jurisprudential authority is constitutionally empowered over all economic and financial affairs, has produced a hybrid economic system that is simultaneously ideologically constrained and structurally resilient. While the doctrinal foundations of Islamic economics, rooted in the prohibition of ribā (interest), the obligations of zakāt (alms tax), and the principle of adl (justice), provide a normative framework for economic governance, empirical evidence demonstrates that successive rounds of United States-led sanctions, particularly from 2012 and following the reimposition of maximum pressure in 2018, have severely disrupted macroeconomic performance. Per capita GDP declined from approximately USD 8,000 in 2012 to USD 5,000 by 2024 (World Bank, 2024), annual inflation reached 40–50% by 2023–2024, and the Iranian middle class contracted by an estimated 17–28 percentage points between 2012 and 2019. This study contributes to the literature by systematically situating these macroeconomic dislocations within the ideological parameters of the Wilāyat al-Faqīh governance model and assessing the adaptive strategies deployed by the state. The study discusses the policy implications for sanctions design, Islamic economic reform, and institutional resilience.